2017
DOI: 10.1186/s12885-016-3043-1
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer is an essential accompaniment of circulating tumor cells in gastric cancer

Abstract: BackgroundFibrinogen (FIB) is an important source of fibrin, which plays a crucial role in circulating tumor cells (CTCs) extravasation and distant metastasis development. We hypothesize it’s stable final product, plasma D-dimer, may be associated with CTCs appearance and can reflect the metastatic phenotype in cancer patients.MethodsWe first verified our hypothesis in different murine gastric cancer metastasis models in vivo, plasma D-dimer and fibrinogen as well as its degradation products were directly exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…Previous studies reported that d-dimer elevated in cancer patients with absence of VTE and high d-dimer level was associated with poor prognosis [27][28][29]. Potential mechanism of d-dimer elevation in malignancy might associated with circulating tumor cells clots [30]. The present findings and the previous reports suggest that d-dimer is not a predictor of VTE in AGC patients.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies reported that d-dimer elevated in cancer patients with absence of VTE and high d-dimer level was associated with poor prognosis [27][28][29]. Potential mechanism of d-dimer elevation in malignancy might associated with circulating tumor cells clots [30]. The present findings and the previous reports suggest that d-dimer is not a predictor of VTE in AGC patients.…”
Section: Discussionsupporting
confidence: 51%
“…China has more GC patients than any other country and due to high rate of migration, invasion, and drug‐resistance, and currently, patients in an advanced stage of the GC have a poor survival rate . Epithelial‐mesenchymal transition (EMT) is a phenomenon in which epithelial cells change into mesenchymal cells in both normal or pathological conditions and more, and more research indicates that the EMT phenomenon has an important role in the transition from early to invasive carcinomas .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported a positive association between circulating tumor cells and plasma D-dimer levels in patients with metastatic breast cancer (35,36). Diao et al (37) observed that plasma D-dimer levels were markedly increased in gastric cancer patients with distant metastases, particularly in patients with visceral metastases. In fact, they suggested D-dimer to be a promising predictor of clinical stage in the gastric cancer patients (37).…”
Section: Discussionmentioning
confidence: 99%
“…Diao et al (37) observed that plasma D-dimer levels were markedly increased in gastric cancer patients with distant metastases, particularly in patients with visceral metastases. In fact, they suggested D-dimer to be a promising predictor of clinical stage in the gastric cancer patients (37). Lee et al (38) reported that increased plasma D-dimer and fibrinogen degradation product levels were significantly associated with TNM stage in colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%